Intervention Of Ambon Banana Blossom As An Alternative Food To Reduce Blood Glucose Levels In Diabetic Patients In The Working Area Of Kemalo Abung Health Center - Ari Khusuma; Annisa Agata; Arini Pradita Roselyn; Annisa Mulia Annasis (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: The prevalence of diabetes in Indonesia based on the results of the Riskesdas in 2013 is 2.1%; the figure is higher compared with the year 2007 (1.1%). Complications in people with diabetes occur due to uncontrolled blood glucose increases. The necessity of controlling glucose is easily obtainable and cheap, such as granting high fiber with Ambon's Banana as in Pringsewu Regency. This research aims to know the influence of consuming refined Ambon's Banana blossom against the decrease in blood glucose levels in people with diabetes. Research Methods: Types of quantitative research and analysis by a quasi-experimental approach. The population in this research is a citizen who lived in the region of clinics Abung Kemalo Kab. North Lampung affected by diabetes mellitus amounted to 116 people. Sample 10 people. Analysis of a t-test using the bivariate test. Research Result: The results showed the average blood glucose level before the banana blossom given to the intervention group was 224.4. While in the group, the control was 280.4. After the banana blossom preparations were given in the intervention group, average blood glucose levels were 172. At the same time, the control group was 251.0. Conclusion: There is a difference between consuming the refined Ambon's banana blossom and not consuming the refined Ambon's banana against the decrease in blood glucose levels in people with diabetes (p-value 0.022). This research is expected to advise health workers should be socialized heart Ambon's banana as an alternative for patients with DM.